Happiness and Utility Essays Presented to Frederick Rosen - Varouxakis, Georgios; Philp, Mark (UCL Press, 2019)
Happiness and Utility brings together experts on utilitarianism to explore the concept of happiness within the utilitarian tradition, situating it in earlier eighteenth-century thinkers and working through some of its developments at the end of the nineteenth and beginning of the twentieth centuries. Drawing on a range of philosophical and historical approaches to the study of the central idea of utilitarianism, the chapters provide a rich set of insights into a founding component of ethics and modern political and economic thought, as well as political and economic practice. In doing so, the chapters examine the multiple dimensions of utilitarianism and the contested interpretations of this standard for judgement in morality and public policy.